O conservadorismo incondicional e a convergencia das práticas contábeis brasileiras às IFRS - Castro, Lívia Arruda (2011)
This research investigates the amendments on Brazilian accounting standards and the unconditional conservatism effects of the financial statements issued by public companies which publishes their reports under Brazilian standards and international standards. In the context of Brazilian accounting harmonization into International Financial Reporting Standards (IFRS), this study examined whether the adoption of these standards has conducted to more conservative financial statements, which indicate higher quality. It was selected out 55 companies, comprising 21 listed in NYSE and 34 listed in BM&FBovespa, which resulted in a sample of 196 net profits and losses and 204 shareholders’ equities issued under Brazilian Standards and international standards (IFRS or US GAAP), during the period 2005 to 2009, range when was issued the Law nº 11.638/2007, which has introduced significant amendments on Brazilian accounting standards, in order to match to the international standards. In order to examine the conservatism levels, it was calculated the conservatism index (GRAY, 1980) to the net profits and losses and shareholders’ equities sampled. Through the statistic test tool of hypothesis of differences of averages, the results disclosed, mostly, that the financial statements measured under Brazilian standards are more conservative than those under international standards (IFRS and US GAAP). This study also revealed the compliance of Brazilian accounting into IFRS did not affected significantly the levels of conservatism of the net profits and losses shareholders’ equities measured under Brazilian accounting standards.